Safety of oral graded challenges as a diagnostic approach hypersensitivity reaction to anti-tuberculosis drugs: a case report - Dwipayana, Putu Aditya; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
Tuberculosis (TB) still becomes a significant health problem in developing countries, especially in Indonesia. Allergy to antitubercular drugs is a real hindrance to the management of TB. The first-line anti-TB drug (ATD) is still the most effective TB drug, but it can have some side effects. One of these side effects is drug hypersensitivity reactions (DHR) which can affect a patient's compliance. The recommended diagnostic approach to DHR is a graded challenge by introducing drugs safely and optimally under a threshold dose until the usual daily dose is reached. We present a case of DHR to ATB drug and oral graded challenge as the diagnosis approach.